A square peg in a round hole inclusion for every child - Tallent, Linda; Thompson, Jean (London Featherstone Education, 2011)
This book identifies the barriers that children with a wide range of different additional needs experience in school. It provides case studies of each of the major conditions, describes the behaviour of the child involved and the process of diagnosis, concluding with practical strategies on how to help these children become successful learners.
Chapter 1. Identifying reasons for differences in behaviour -- Chapter 2. Speech, language and communication -- Chapter 3. Austitic spectrum disorder -- Chapter 4. Difficulties with reading, writing, spelling and maths -- Chapter 5. Dyspraxia or developmental coordination disorder (DCD) - Chapter 6. Attention Deficit (Hyperactivity) Disorder (AD(H)D) -- Chapter 7. The inclusive learning environment.
Includes bibliographical references (page 80).
Keywords: Children with disabilities -- Education -- Great Britain